2022
DOI: 10.1007/s12192-022-01266-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lycium barbarum glycopeptide on renal and testicular injury induced by di(2-ethylhexyl) phthalate

Abstract: Di(2-ethylhexyl) phthalate (DEHP) is a common environmental pollutant with renal and reproductive toxicity. Lycium barbarum glycopeptide (LbGp) is the main active component of Lycium barbarum, which can protect the kidney and promote reproduction. Autophagy and apoptosis are the regulatory mechanisms of cell adaptation to external stress. This study investigated whether DEHP and LbGp affect kidney and testis by regulating autophagy and apoptosis. DEHP induced apoptosis in human embryonic kidney-293 (HEK-293) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Here, we revealed that the creatinine levels of DEHP-exposed mice were significantly higher than those of the control group. However, our previous study [21] did not discuss the deterioration of renal function in the model group due to the short time (2 weeks) required for establishing the DEHP model. Li et al [36] reported that mice treated with 1,000 mg/kg/bw DEHP or 500 mg/kg/ bw DEHP showed significantly higher serum creatinine, urea nitrogen, and uric acid levels than untreated mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Here, we revealed that the creatinine levels of DEHP-exposed mice were significantly higher than those of the control group. However, our previous study [21] did not discuss the deterioration of renal function in the model group due to the short time (2 weeks) required for establishing the DEHP model. Li et al [36] reported that mice treated with 1,000 mg/kg/bw DEHP or 500 mg/kg/ bw DEHP showed significantly higher serum creatinine, urea nitrogen, and uric acid levels than untreated mice.…”
Section: Discussionmentioning
confidence: 99%
“…First, we found that the kidney indices of the model group were significantly lower than those of the control group, whereas the kidney indices of the treatment group receiving GTPs reversed DEHP-induced kidney damage. We have previously reported [21] that DEHP can reduce the kidney indices of the mice in the DEHP model group. Here, we revealed that the creatinine levels of DEHP-exposed mice were significantly higher than those of the control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After 1 wk of acclimatization, 50 mice were randomly assigned into the following five groups (10 mice/group): Control group, administered with 0.2 mL distilled water; model group, administered with 0.2 mL corn oil and DEHP (1500 mg/kg bodyweight); treatment group, administered with 0.2 mL corn oil and DEHP (1500 mg/kg bodyweight), followed by administration of 0.2 mL GTPs (70 mg/kg bodyweight) after 1 h; oil group, administered with 0.2 mL corn oil; GTP group, administered with 0.2 mL GTP (70 mg/kg bodyweight). Based on our previous study, DEHP[ 25 ] and GTPs[ 26 ] were gavaged. The doses were adjusted weekly based on the bodyweight of the mice.…”
Section: Methodsmentioning
confidence: 99%